2013
DOI: 10.1186/1471-2431-13-1
|View full text |Cite
|
Sign up to set email alerts
|

Persistent wandering atrial pacemaker after epinephrine overdosing – a case report

Abstract: BackgroundLong-term complications of sympathomimetic drug overdosing have not been adequately investigated in infants and young children. Despite reports discouraging their use in children, these formulations are frequently administered for “cold-like symptoms”. Their frequent adverse events are different forms of arrhythmias, including multifocal atrial tachycardia.Case presentationA 3-year-old toddler developed multifocal atrial tachycardia following an iatrogenic overdose of epinephrine accidentally adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
102
3
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(115 citation statements)
references
References 6 publications
9
102
3
1
Order By: Relevance
“…Adolescents in smaller practices were less likely to receive Tdap vaccine, but more likely to receive influenza vaccine. These findings confirm an earlier study among children in which likelihood of influenza vaccination was increased with smaller office size, 21 although the definition of smaller practice was considerably larger (<5000 patients) than in the current study. However, the practice sizes in this study accounted for patients ages 11–17 years only, not all children.…”
Section: Discussionsupporting
confidence: 89%
“…Adolescents in smaller practices were less likely to receive Tdap vaccine, but more likely to receive influenza vaccine. These findings confirm an earlier study among children in which likelihood of influenza vaccination was increased with smaller office size, 21 although the definition of smaller practice was considerably larger (<5000 patients) than in the current study. However, the practice sizes in this study accounted for patients ages 11–17 years only, not all children.…”
Section: Discussionsupporting
confidence: 89%
“…Secondary analysis of the most recent Nepal DHS revealed that mothers who attended four or more antenatal care visits were more likely to feed their children in accordance with recommended frequency (Khanal et al . 2013). Additionally, a review of strategies aimed to improve complementary feeding found that educational interventions improved feeding practices and had a positive impact on child growth within populations that were food secure (Imdad 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In low-income countries, sources have been less well examined. For rural households in Egypt, the presence of poultry manure, uncovered litter in house yards and lack of barriers to keep animals out of houses have been identified as risk factors for Campylobacter infection in children [15, 16], while a study carried out in Ethiopia identified exposure to domestic animals as a sufficient risk factor for infection [17]. …”
Section: Introductionmentioning
confidence: 99%